Analysis of image of politicians today and the acceptance of the people in Chaiyaphum Province - Sawadrath, Narat; Sanguansin, Samurt (Dhammathas Academic Journal, 2023)
The objectives of this research were to study the current image, the factors of acceptance and analyze the guidelines for creating of a good politician’s image according to Buddhist principles. This research was mixed method research: qualitative and quantitative researches by study from related documents and In-depth interviews 35 key informants. Data were analyzed by inductive method. For quantitative research, data were collected from 400 samples by using of a questionnaire and analyzed by descriptive statistics. The results showed that: 1. The image of a politician must have 1) morality and ethics, i.e. must have a good behavior and Family members should also have an unblemished history; 2) human relations, i.e. should be a native people and able to communicate and understand local customs and culture at well; 3) Highly educated, i.e. able to be depended on be an agent in bringing prosperity to the community. 2. The factors of public acceptance of politicians were 1) Motivation which arising from acceptance or admiration of politicians, have a visiting and conversation with the people in local language 2) Background of politicians who used to be politicians or former senior government officials. 3) Political attitude which accepts more individuals than political parties. 3. Guidelines for creating a good politician’s image according to Buddhist principles consist of 1) Motivation, having secular principles, namely (1) Caga: giving and sacrifice (2) Tama: self-training, self-restraint, and control own emotions 2) Background of politicians, there are secular principles, namely (1) truthfulness and (2) virtue as a guideline for practice with honesty, honesty, speaking the truth, doing the truth and reject inaccuracy; 3) Political attitudes There are secular principles: (1) having patience: patience in fighting hardships in order to create good deeds in good faith, and (2) having faith in making good deeds manifest tolerant of criticism and will always practice.